Exploring the Role of Maujana Nagori (BPD) in Implementing Village Government in Merdeka District, Karo Regency: A Mixed-Methods Study - Bahtiar Panggabean Damanik (IHSA Institute, 2024)
This research seeks to explore the role of Maujana Nagori (BPD) in implementing village government in Merdeka District, Karo Regency, Indonesia. The BPD is a crucial institution in the decentralized governance structure of Indonesia, tasked with representing the interests of the local community, advising village heads, and facilitating decision-making processes. The research employs a mixed-methods approach, combining qualitative and quantitative methods to gather rich, nuanced data on the BPD's functions, effectiveness, and challenges within the local governance structure. The findings of the analysis reveal that the BPD plays a critical role in promoting participatory democracy, fostering inclusive development, and strengthening governance institutions at the grassroots level. However, the effectiveness of the BPD is hampered by challenges such as limited resources, capacity constraints, and bureaucratic hurdles. Based on the findings, several recommendations are proposed to enhance the effectiveness of the BPD, including capacity-building programs, access to resources and expertise, transparency and accountability, and promoting community participation and engagement.